(untitled) (Research, Society and Development, 2021)
The present study aims to highlight the effects of ozone therapy as an integrative and non-surgical complementary treatment for periodontal diseases. This is an integrative literature review, in which Medline, Lilacs, EBSCOHost and Cochrane databases were searched, using the descriptors "ozone", "ozone therapy" and "periodontal disease" published between 2011 and 2021, being chosen 20 articles to compose the study. Ozone is a gas formed by three oxygen atoms and, due to its instability, it is considered one of the largest oxidizing agents in the world, which allows this gas to be used for various therapeutic purposes. This substance has important antimicrobial effects against gram-negative bacteria, which play a strong role in the etiology of periodontal diseases. In addition, it has a broad spectrum of activity, but with low toxicity and does not cause bacterial resistance. Ozone therapy is an efficient integrative treatment that complements scaling and root planing, which can sometimes be insufficient in the treatment of periodontal diseases. However, further studies must be carried out to assess and determine clinicians’ parameters of ozone.